1995
DOI: 10.1200/jco.1995.13.3.645
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of docetaxel for advanced or metastatic platinum-refractory non-small-cell lung cancer.

Abstract: Docetaxel administered at 100 mg/m2 intravenously every 3 weeks has notable activity against platinum-refractory non-small-cell lung cancer, with a 21% major response rate. Primary side effects were neutropenia, hypersensitivity, and fluid retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(68 citation statements)
references
References 16 publications
3
64
0
1
Order By: Relevance
“…The response rate in our study (37%; 95% CI, 24-49) seems very promising and is higher than the reported 16-22% in phase II studies for single-agent docetaxel as second-line treatment [13][14][15]. Fossella et al found in a randomised phase III trial response rates of 11 and 7% for single-agent docetaxel 100 and 75 mg/m 2 every 3 weeks, respectively [17].…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…The response rate in our study (37%; 95% CI, 24-49) seems very promising and is higher than the reported 16-22% in phase II studies for single-agent docetaxel as second-line treatment [13][14][15]. Fossella et al found in a randomised phase III trial response rates of 11 and 7% for single-agent docetaxel 100 and 75 mg/m 2 every 3 weeks, respectively [17].…”
Section: Discussionsupporting
confidence: 40%
“…The activity of new cytotoxic drugs such as gemcitabine, vinorelbine and paclitaxel in second-line setting is not well defined [5][6][7][8][9][10][11][12]. Most promising experience in second-line chemotherapeutic treatment of NSCLC is with docetaxel, which in phase II studies showed favourable tumour responses ranged from 16 to 22% [13][14][15]. However, a randomised study with docetaxel at a dose of 75 mg/m 2 compared to best-supportive care showed a lower response rate (7%), but still a significant improvement in survival and quality of life, without an excess of toxicity [16].…”
Section: Introductionmentioning
confidence: 99%
“…The most promising data were shown for chemotherapy with docetaxel and Pemetrexed (Hanna et al, 2004). Those drugs showed consistently good survival data in pretreated patients and represent the treatment of choice in second-line setting (Fossella et al, 1995(Fossella et al, , 2000b. Over the last years, also newly developed drugs such as EGFR or VEGFR blocking agents were introduced for second-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, new drugs with demonstrated activity against NSCLC, such as the taxanes (Gatzemeier et al, 1995;Fossella et al, 1995), topoisomerase inhibitors (Fukuoka et al, 1992), gemcitabine (Noble and Goa, 1997) and vinorelbine (Lilenbaum and Grece, 1993;Goss et al, 1997) have aroused considerable interest. In particular, vinorelbine has been shown to increase survival in patients aged more than 70 years in comparison with the best supportive care alone (ELCVISG, 1999), and the favourable toxicological profile of gemcitabine allows its use in both unfit and elderly patients.…”
mentioning
confidence: 99%